The Garbage, the Castle, its Lord & the Queen - Rainer Atzbach (Danish Journal of Archaeology, 2023)
This paper seeks to explore an alternative approach to the interpretation of paradoxal evidence by comparing finds and contexts. It is based upon the theorems of garbology, developed by the archaeologist William Rathje (1945-2012) in the Tucson Garbage Project. While Rathje used archaeological methods for research in garbage reflecting modern consumerism, this paper takes the opposite approach, applying the theorems of garbology to late medieval garbage practices. A case study focusing on Boringholm Castle (lifespan between 1369 and the early 15th century) discusses the paradox of finding artefacts reflecting an outstanding elite culture in a modest environment that resembles a farmstead rather than a late medieval castle. The range of finds at Boringholm is very broad, demonstrating that this was the household of a parvenu who tried to imitate a courtly lifestyle.